2013
DOI: 10.5993/ajhb.37.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Activity Patterns and Perceptions About Active Transport to School

Abstract: Active transport programs will likely have a greater impact on before-school activity than after school. Perceptions concerning active transport should be assessed, and parent/child discrepancies rectified prior to program implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A wide range of instruments were used to determine PAP including accelerometers [ 8 , 9 , 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], pedometers [ 22 , 57 , 58 , 59 , 60 , 61 , 62 ], heart rate monitors [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], questionnaires/diaries [ 10 , 11 , 27 , 72 , 73 , 74 , 75 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of instruments were used to determine PAP including accelerometers [ 8 , 9 , 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], pedometers [ 22 , 57 , 58 , 59 , 60 , 61 , 62 ], heart rate monitors [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], questionnaires/diaries [ 10 , 11 , 27 , 72 , 73 , 74 , 75 ...…”
Section: Resultsmentioning
confidence: 99%
“…In other words, researchers were primarily focussed on describing/identifying the amount of time (or the percentage of time) children spent in PA of different intensities (including sedentary behaviour). The main idea was to determine how these activities vary across the day (considering different segments of the day) [ 14 , 28 , 29 , 35 , 39 , 41 , 42 , 44 , 46 , 47 , 53 , 56 , 85 , 86 , 89 ], across week and weekend days [ 12 , 14 , 29 , 30 , 33 , 39 , 41 , 43 , 44 , 45 , 47 , 48 , 50 , 55 , 56 , 85 , 86 ], or even how children respond to an intervention program [ 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (35.9%) did not find any statistically significant (significant for short hereafter) perceived barriers to child’s ACS in their analyses. For the other 25 studies, we further excluded four studies (10.3%) that reported perceived barriers based on descriptive or bivariate statistics [ 36 , 51 , 52 , 63 ], one study that measured single item (i.e., perceived safety) [ 47 ], and one study that used summary index (i.e., 11 items for parental concerns with the mean calculated) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite these benefits, it is not well understood how environmental and social factors are associated independently or collectively with the adoption of AT behavior in youth. Some research has shown that built environmental factors (e.g., neighborhood street connectivity, land use, urbanicity) and social factors (e.g., family time constraints, adolescent fear coping, parental risk perceptions) can influence adolescent AT patterns [ 26 , 27 , 28 , 29 , 30 , 31 ]. Most youth AT research has emphasized walking and cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, modes of access that allow more direct physical engagement with community, such as with AT, further contribute to developing a “sense of community”. Some research has demonstrated that built environment factors (e.g., neighborhood street connectivity, land use, urbanicity) and sociodemographics (e.g., race/ethnicity, income) can influence AT behaviors and attitudes [ 26 , 27 , 28 , 29 , 30 , 31 , 38 ]. However, the dynamic relationship of these contextual effects, along with “sense of community”, has not been extensively explored, especially in a regionally diverse area such as Washington, D.C.…”
Section: Introductionmentioning
confidence: 99%